Women of marginalised communities : concerns about exclusion - Women of Marginalised Communities: Concerns about Exclusion (Seminar) (2018 : Aligarh, India); Musavi, Azra.; Gupta, Juhi.; Aligarh Muslim University. Advanced Centre for Women's Studies (New Delhi : Sarup Book Publishers (P) Ltd., 2020)
Papers presented at National Seminar on the theme "Women of Marginalised Communities: Concerns about Exclusion" was organized by the Advanced Centre for Women's Studies, Aligarh Muslim University from November 14th-16th, 2018, sponsered by the Indian Council of Social Sciences Research.
Includes bibliographical references and index.
Keywords: Women with social disabilities -- India -- Congresses; Women with social disabilities -- Education -- India -- Congresses; Women with social disabilities -- Legal status, laws, etc. -- India -- Congresses; Marginality, Social -- India -- Congresses; Marginality, Social; Women with social disabilities; India; Conference papers and proceedings